2022
DOI: 10.3390/ijerph19116855
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of High-Intensity Interval Training (HIIT) on Endurance and Strength Parameters in Children and Adolescents

Abstract: High-Intensity Interval Training (HIIT) promises high training effects on aerobic fitness in children, adolescents and adults in a relatively short time. It is therefore well-established in professional training settings. HIIT methods could also be suited to Physical Education (P.E.) lessons and contribute to students’ health and fitness. Since HIIT sessions need little time and equipment, they can be efficiently implemented in P.E. However, there are few studies which have examined non-running-based HIIT prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…Research has shown the ability of R-HIIT in the school setting to improve aerobic endurance (Bauer et al, 2022;Harnish et al, 2022). Our study found that B-HIIT also improved cardiorespiratory fitness in adolescents, which is consistent with other studies (Paulino da Silva Bento et al, 2021;Bossmann et al, 2022). Cardiac adaptation through HIIT training can explain why resistance exercises based on body weight can lead to similar aerobic fitness as running-based programs.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Research has shown the ability of R-HIIT in the school setting to improve aerobic endurance (Bauer et al, 2022;Harnish et al, 2022). Our study found that B-HIIT also improved cardiorespiratory fitness in adolescents, which is consistent with other studies (Paulino da Silva Bento et al, 2021;Bossmann et al, 2022). Cardiac adaptation through HIIT training can explain why resistance exercises based on body weight can lead to similar aerobic fitness as running-based programs.…”
Section: Discussionsupporting
confidence: 92%
“…Various peripheral and central physiological factors could explain the elevated VO 2max after HIIT intervention (Bossmann et al, 2022). In this study, the possible reason why B-HIIT is superior to R-HIIT is that B-HIIT requires the recruitment of more fast muscle fibers as well as the mobilization of all types of muscle during exercise, thus leading to more blood lactate and consequently to an increase in VO 2max (Binzen et al, 2001).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations